Comparison of pneumatic lithotripsy versus laser lithotripsy for upper ureteral calculi - Galeti, Ershad Hussain; Shahab, Saqib; Bharali, Mriganka Deuri (International Surgery Journal, 2021)
Background: Several modalities are available for upper ureteric stone fragmentation. From them pneumatic and holmium: yttrium-aluminum-garnet lithotripsy has favourable outcomes. In this study we studied 50 patients who underwent ureteroscopic pneumatic lithotripsy or laser lithotripsy. This study aims to to compare the outcome of PL and LL in the management of upper ureteric calculi. Methods: This is a prospective, randomized study of 50 cases; 25 cases of TUL with pneumatic lithotripter and 25 cases of TUL with laser lithotripter over two years. The purpose of this study was to analyze the factors predicting the stone-free rate, assess the complications following PL and LL, and assess the need for a second procedure if retropulsion of calculi occurs. Results: Two groups were similar in age, gender, mean size of stones, retropulsion and complications. There was a statistical difference in terms of stone free rate in favour of LL group (p≤0.05) and mean operative time in favor of the PL group (p≤ 0.05). Conclusions: In conclusion, we found that both the PL and LL approaches were effective and safe for upper ureteric calculi, but the LL method had advantages, especially in stone free rate, over the PL treatment. Another advantage of the LL method was safe stone fragmentation in upper ureteral calculi due to lower retropulsion rate in contrast with the PL method.